The Question of Public Participation in the Procedure for Authentic Interpretation of Laws - Struić, Gordan (Review of European and Comparative Law, 2021)
Authentic interpretation of laws is an interpretation of legal provisions that, due to their lack of clarity or misinterpretation in their application, is provided by the parliament. Unlike the legislative procedure, which is conducted, as a rule, in two (exceptionally three) readings, a proposal for giving an authentic interpretation is discussed in one reading. Starting from the understandings of some authors that the act of authentic interpretation of laws is contrary to the principle of democratic pluralism, and that it lacks the necessary level of democratic control and citizen participation, the author examines whether the Croatian parliamentary law enables public participation in the procedure for authentic interpretation of laws and, if so, what legal instruments can be used to implement it in parliamentary practice. To this end, the paper analyzes several relevant constitutional, legal, and procedural provisions of the Croatian parliamentary law, with reference to a parliamentary practice. Given the fact that the procedure for authentic interpretation in the Republic of Croatia, the Republic of Northern Macedonia, the Republic of Slovenia and the Republic of Serbia is regulated in a similar way by the rules of procedure of their respective parliaments, the relevant regulations of the latter three countries on the possibility of public participation in this procedure are analyzed as well. It was concluded that Croatian parliamentary law enables public participation in the procedure for authentic interpretation, through the instruments of petition, information and involvement in working groups and working bodies, and the same instruments, with certain specifics, are recognized in the parliamentary law of the latter three countries.